Sweat the Fall Stuff: Physical Activity Moderates the Association of White Matter Hyperintensities With Falls Risk in Older Adults - Crockett, Rachel A.; Falck, Ryan. S.; Dao, Elizabeth; Hsu, Chun Liang; Tam, Roger; Alkeridy, Walid; Liu-Ambrose, Teresa (Frontiers in Human Neuroscience, 2021)
Background: Falls in older adults are a major public health problem. White matter hyperintensities (WMHs) are highly prevalent in older adults and are a risk factor for falls. In the absence of a cure for WMHs, identifying potential strategies to counteract the risk of WMHs on falls are of great importance. Physical activity (PA) is a promising countermeasure to reduce both WMHs and falls risk. However, no study has yet investigated whether PA attenuates the association of WMHs with falls risk. We hypothesized that PA moderates the association between WMHs and falls risk. Methods: Seventy-six community-dwelling older adults aged 70–80 years old were included in this cross-sectional study. We indexed PA using the Physical Activity Score for the Elderly (PASE) Questionnaire. Falls risk was assessed using the Physiological Profile Assessment (PPA), and WMH volume (mm3) was determined by an experienced radiologist on T2-weighted and PD-weighted MRI scans. We first examined the independent associations of WMH volume and PASE score with PPA. Subsequently, we examined whether PASE moderated the relationship between WMH volume and PPA. We plotted simple slopes to interpret the interaction effects. Age, sex, and Montreal Cognitive Assessment (MoCA) score were included as covariates in all models. Results: Participants had a mean age of 74 years (SD = 3 years) and 54 (74%) were female. Forty-nine participants (66%) had a Fazekas score of 1, 19 (26%) had a score of 2, and 6 (8%) a score of 3. Both PASE (β = −0.26 ± 0.11; p = 0.022) and WMH volume (β = 0.23 ± 0.11; p = 0.043) were each independently associated with PPA score. The interaction model indicated that PASE score moderated the association between WMH volume and PPA (β = −0.27 ± 0.12; p = 0.030), whereby higher PASE score attenuated the association between WMHs and falls risk. Conclusion: PA is an important moderator of falls risk. Importantly, older adults with WMH can reduce their risk of falls by increasing their PA.